Tuberculous Pleuro-Pericardial Effusion with Adenitis - VO, Adeyeye; KO, Aramide; AP, Adefalujo; OO, Ayodele (Archives of Clinical and Medical Case Reports, 2017)
Background: Hydra-headed clinical presentations of tuberculosis could be confusing even in immunocompetent, for example pleuro-pericardial effusion with adenitis. From our literature search, this is rare. Case presentation: A 61-year-old clergyman presented with a 3-week history of cough, fever and a 5-day history of progressive dyspnoea. There was associated anaemia, weight loss but no history of drenching night sweat, hemoptysis, exposure to tuberculosis, diabetes or other suggestion of immunosuppression. Examination revealed multiple matted left axillary lymph nodes. Erythrocyte sedimentation rate (ESR) was 70 mm/hr; and negative for Hepatitis B, C and HIV. Chest X-ray showed left lower lung zone homogenous opacity with obliteration of the left cardiac border. Lymph node aspirate and pleural fluid analyses confirmed a tuberculous aetiology. Conclusion: Tuberculous pleuro-pericardial effusion with adenitis occurs in immunocompetent. High index of suspicion in endemic areas as well as early anti-tubercular treatment could be life-saving.